Studentská geologická konference 2022 Sborník abstraktů - Sobek, Kamil; Pořádek, Přemysl; Cígler, Vojtěch; Nečas, Petr (Masaryk University Press, 2022)
Title in English: Student geological conference 2022: Conference proceedings Student geological conference proceedings. Conference was held at Faculty of Science, Masaryk University in Brno on June 3rd 2022. Department of Geological Sciences was organizer in cooperation with the Czech Geological Society.